Plastic concrete mixture for dam anti-seepage continuous wall construction and preparation method
By using a specific proportion of water-expanded water stop strips, calcium carbonate whiskers, calcium sulfate whiskers, steel fibers, asbestos and dispersants in the construction of dam seepage-proof continuous walls, the problem of poor crack resistance and durability of plastic concrete is solved, and the high performance and long life of concrete in harsh environments is achieved.
Patent Information
- Application Number
- CN202411917326.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-04
AI Technical Summary
In the construction of dam seepage-proof continuous walls, plastic concrete has poor crack resistance and durability, which is difficult to meet actual use needs, especially in harsh environments, service life and safety are challenged.
A specific proportion of water-expanded water stop strips, calcium carbonate whiskers, calcium sulfate whiskers, steel fibers, asbestos and dispersants are used to coordinate the combination. The dispersant is conducive to the more uniform dispersion and coordination of the filler, so that the concrete has better crack resistance and durability when under pressure and bending force.
While maintaining a low elastic modulus, it improves the crack resistance and durability of concrete, extends the service life of concrete, and improves its safety in harsh environments.
Smart Images

Figure BDA0005207114340000081 
Figure BDA0005207114340000091
Abstract
Description
Technical Field
[0001] The invention relates to the field of concrete, in particular to a plastic concrete mixture used for the construction of a dam anti-seepage continuous wall and a preparation method thereof. Background Art
[0002] The dam anti-seepage continuous wall is an important anti-seepage structure used in dam construction. It mainly refers to the continuous pouring or construction of a high-density, high-strength wall in the dam foundation or dam body to prevent water from penetrating, thereby ensuring the safety and stability of the dam.
[0003] In order to better adapt to the deformation of the foundation and dam body and avoid wall cracking, the dam anti-seepage continuous wall is usually constructed with plastic concrete mixture. However, in order to maintain its low elastic modulus, the amount of cement used in plastic concrete is usually much lower than that of ordinary concrete, which easily leads to poor crack resistance and durability of plastic concrete, making it difficult to meet actual use requirements. In particular, the dam anti-seepage continuous wall is in a relatively harsh environment such as the dam body for a long time, and its service life and safety are greatly challenged. Summary of the invention
[0004] In order to better maintain the low elastic modulus of plastic concrete while better improving the crack resistance and durability of plastic concrete, the present application provides a plastic concrete mixture and a preparation method for the construction of a dam anti-seepage continuous wall.
[0005] In the first aspect, the present application provides a plastic concrete mixture for the construction of a dam anti-seepage continuous wall, which adopts the following technical solution: A plastic concrete mixture for the construction of a dam anti-seepage continuous wall, comprising the following components in parts by mass: 115-125 parts of cement; 235-245 parts of water; Sand 770-790 parts; 770-790 parts of crushed stone; Clay 170-190 parts; 35-45 parts of bentonite; 10-15 pieces of water-swelling waterstop strips; Calcium carbonate whiskers 5-10 parts; Calcium sulfate whiskers 5-10 parts; 5-8 parts of steel fiber; 3-6 parts of chrysotile; Dispersant 10-15 parts.
[0006] By adopting a specific proportion of water-swellable waterstop strips, calcium carbonate whiskers, calcium sulfate whiskers, steel fibers, chrysotile asbestos and dispersants for synergistic compounding, the dispersant is conducive to more uniform dispersion of the filler in the concrete mixture, which is conducive to better coordination between the fillers. When the concrete is subjected to pressure, the calcium carbonate whiskers, calcium sulfate whiskers and steel fibers can produce a certain deformation with the help of the flexibility of the water-swellable waterstop strips and chrysotile asbestos, so that the low elastic modulus of the concrete is not easily affected. At the same time, the calcium carbonate whiskers, calcium sulfate whiskers, steel fibers and chrysotile asbestos make the concrete less likely to break when subjected to bending force, which is conducive to improving the crack resistance of the concrete. The water-swellable waterstop strips will also expand when encountering water to increase the density of the concrete, which is conducive to better extending the durability of the concrete. In addition, the above-mentioned fillers can be stacked more densely in the concrete under the dispersing effect of the dispersant, which is conducive to better improving the density of the concrete, so that the plastic concrete has better impermeability and durability while maintaining a low elastic modulus.
[0007] Preferably, the dispersant is compounded from acrylic copolymer emulsion, sodium methyl siliconate, sodium stearate and calcium chloride.
[0008] By compounding the above-mentioned components to form a dispersant, it is beneficial for the water-swelling waterstop strips, calcium carbonate whiskers, calcium sulfate whiskers, steel fibers and chrysotile asbestos to be dispersed more evenly in the concrete mixture, which is beneficial for the above-mentioned fillers to be better compounded to play a better role. At the same time, it is beneficial for the stacking of fillers to be more compact, which is beneficial for better maintaining the low elastic modulus of concrete while better improving the crack resistance and durability of concrete; at the same time, the dispersant formed by the compounding of the above-mentioned components is also beneficial for better forming a waterproof film to better improve the waterproof performance of concrete, thereby further improving the anti-seepage performance and durability of concrete.
[0009] Preferably, the dispersant is prepared by compounding acrylic copolymer emulsion, sodium methyl siliconate, sodium stearate and calcium chloride in a mass ratio of (4-6): (3-4): (2-3): (1-2).
[0010] By adopting a specific proportion of acrylic copolymer emulsion, sodium methyl siliconate, sodium stearate and calcium chloride to form a dispersant, it is beneficial to better improve the dispersibility of the filler, making the stacking of the fillers more dense, and at the same time, it is also beneficial for the water-swelling waterstop to better cooperate with other fillers, making the concrete both rigid and flexible without affecting each other, which is beneficial to better maintain the low elastic modulus of the concrete while also helping to better improve the concrete's impermeability and durability.
[0011] Preferably, the water-swellable waterstop strip is in granular form.
[0012] Preferably, the particle size of the water-swellable waterstop strip is 2-5 mm.
[0013] By cutting the water-swellable waterstop strip into granules and controlling the particle size of the water-swellable waterstop strip, the water-swellable waterstop strip can be better evenly dispersed in the concrete mixture, which in turn can facilitate better synergistic compounding of the water-swellable waterstop strip with calcium carbonate whiskers, calcium sulfate whiskers, steel fibers and chrysotile asbestos, thereby better maintaining the low elastic modulus of concrete while better improving the concrete's crack resistance and durability.
[0014] Preferably, the surface of the water-swellable waterstop strip particles is also covered with a waterproof coating.
[0015] By covering the surface of the water-swellable waterstop strip particles with a waterproof coating, the water-swellable waterstop strip is not easy to react when mixed with other ingredients to form a concrete mixture, and is not easy to affect the mixing of the concrete mixture. After the concrete mixture solidifies to form concrete, the water-swellable waterstop strip is easy to deform when the concrete adapts to the terrain of the dam and when the anti-seepage continuous wall is under pressure. The waterproof coating on the surface of the water-swellable waterstop strip is destroyed through mutual squeezing between the fillers, thereby expanding when it encounters water and further improving the density of the concrete, thereby improving the concrete's anti-seepage performance and durability.
[0016] Preferably, the length of the calcium carbonate whisker is 30-40 μm and the diameter is 0.5-1 μm; the length of the calcium sulfate whisker is 100-105 μm and the diameter is 1-2 μm.
[0017] Preferably, the steel fiber has a length of 50-60 mm and a diameter of 0.2-0.5 mm.
[0018] By controlling the size of calcium carbonate whiskers, calcium sulfate whiskers and steel fibers, it is beneficial for calcium carbonate whiskers, calcium sulfate whiskers, steel fibers, chrysotile and water-swellable waterstops to work better together, making the stacking of fillers more staggered and dense, so that the concrete can maintain a low elastic modulus while better improving crack resistance and durability.
[0019] In a second aspect, the present application provides a method for preparing a plastic concrete mixture for use in the construction of a dam anti-seepage continuous wall, using the following technical solution: A method for preparing a plastic concrete mixture for use in the construction of a dam anti-seepage continuous wall comprises the following steps: Step 1, first mix cement, sand and gravel and stir evenly, then add water and stir evenly to obtain a premix; Step 2, adding calcium carbonate whiskers, calcium sulfate whiskers, steel fibers, chrysotile asbestos and dispersants into the premix while stirring, stirring evenly, and then adding clay, bentonite and water-swellable waterstop strips in sequence while stirring evenly to obtain a plastic concrete mixture for the construction of a dam anti-seepage continuous wall.
[0020] By controlling the mixing order of the components, the components can be mixed more evenly, which is conducive to better coordination between the fillers, so that the stacking of the fillers when forming concrete is more staggered and denser, which is conducive to better maintaining the low elastic modulus of the concrete while better improving the crack resistance and durability.
[0021] Preferably, in step 2, the water-swellable waterstop strips are pretreated by cutting them into granules, and then the granular water-swellable waterstop strips are immersed in a waterproof coating. After the surfaces of the water-swellable waterstop strips are covered with the waterproof coating, the water-swellable waterstop strips are picked up, dried, and set aside.
[0022] By pretreating the water-swellable waterstop strips, the water-swellable waterstop strips are formed into granules with a waterproof coating on the surface, which is beneficial for the water-swellable waterstop strips to be better dispersed in the concrete mixture so as to better cooperate with other fillers. At the same time, the water-swellable waterstop strips are not easy to affect the mixing of the concrete mixture, which is beneficial for the concrete to better maintain a low elastic modulus while also helping to better improve the concrete's crack resistance and durability.
[0023] In summary, this application has the following beneficial effects: 1. By adopting a specific proportion of water-swelling waterstop strips, calcium carbonate whiskers, calcium sulfate whiskers, steel fibers, chrysotile asbestos and dispersants for synergistic compounding, the dispersant is conducive to more uniform dispersion of fillers in the concrete mixture, thereby facilitating better coordination between the fillers, so that when the concrete is subjected to pressure, the calcium carbonate whiskers, calcium sulfate whiskers and steel fibers can produce a certain deformation with the help of the flexibility of the water-swelling waterstop strips and chrysotile asbestos, thereby making the low elastic modulus of the concrete less likely to be affected. At the same time, the calcium carbonate whiskers, calcium sulfate whiskers, steel fibers and chrysotile asbestos make the concrete less likely to break when subjected to bending force, which is conducive to improving the crack resistance of the concrete. When the water-swelling waterstop strips encounter water, they will also expand to increase the density of the concrete, thereby helping to better extend the durability of the concrete.
[0024] 2. By adopting a specific proportion of acrylic copolymer emulsion, sodium methyl siliconate, sodium stearate and calcium chloride to form a dispersant, it is beneficial to better improve the dispersibility of the filler and better form a waterproof film, thereby better maintaining the low elastic modulus of concrete and better improving the concrete's impermeability and durability.
[0025] 3. By controlling the mixing order of each component, it is beneficial for the components to be mixed evenly, which is beneficial for better coordination between the fillers, so that the stacking of the fillers when forming concrete is more staggered, which is beneficial for better maintaining the low elastic modulus of concrete while better improving the crack resistance and durability.
[0026] 4. By pre-treating the water-swellable waterstop strips, the water-swellable waterstop strips are formed into granules with a waterproof coating on the surface, which is beneficial for the water-swellable waterstop strips to be better dispersed in the concrete mixture so as to better cooperate with other fillers. At the same time, the water-swellable waterstop strips are not easy to affect the mixing of the concrete mixture, which is beneficial for the concrete to better maintain a low elastic modulus while also helping to better improve the concrete's crack resistance and durability. DETAILED DESCRIPTION
[0027] The present application is further described in detail below with reference to the embodiments.
[0028] The materials in the following examples and comparative examples are all commercially available, as follows: Cement was purchased from Fujian Tapai Cement Co., Ltd. as PO42.5 cement; Sand was purchased from Puning Jierun Concrete Co., Ltd., artificial sand, with a fineness modulus of 2.7; The crushed stone was purchased from Hukeng Stone Quarry in Nankou Town, Meixian District, Meizhou City, and the particle size range of the crushed stone was 5-20 mm; Clay was purchased from Malin Mineral Products Processing Plant in Lingshou County, with a particle size of 1250 mesh; Bentonite was purchased from Sichuan Renshou Xingda Industry and Trade Co., Ltd., with a particle size of 800 mesh; The water-expandable waterstop was purchased from Huiding Rubber & Plastic Hengshui Co., Ltd.; Calcium carbonate whiskers were purchased from Xingzhou Mineral Products Processing Plant in Lingshou County; Calcium sulfate whiskers were purchased from Xingzhou Mineral Products Processing Plant in Lingshou County; Steel fibers were purchased from Shandong Hongju Engineering Materials Co., Ltd.; Chrysotile asbestos was purchased from Chengyu Mineral Products Processing Plant in Lingshou County; Acrylate copolymer emulsion was purchased from Jinzhou Baixin Trading Co., Ltd.; Sodium methylsiliconate was purchased from Pandex (Shanghai) International Trading Co., Ltd., CAS No. 16589-43-8; Sodium stearate was purchased from Guangzhou Yisheng Trading Co., Ltd., CAS No. 822-16-2; Acrylic emulsion was purchased from Shandong Junda Chemical Co., Ltd., brand BIT-10; Potassium trimethylsilanol was purchased from Shandong Shouhua Chemical Co., Ltd., CAS No. 10519-96-7; Calcium stearate was purchased from Nanjing Qinghai Trading Co., Ltd., model number Calsan 50; Magnesium carbonate whiskers were purchased from Suzhou Kaifa New Material Technology Co., Ltd.; Magnesium sulfate whiskers were purchased from Xinsheng (Hubei) Chemical Co., Ltd.; Carbon fiber was purchased from Leisu Trading (Shanghai) Co., Ltd.; Slag wool was purchased from Shijiazhuang Tourmaline Mineral Products Co., Ltd.
[0029] Example 1 The present application embodiment discloses a plastic concrete mixture for the construction of a dam anti-seepage continuous wall, which is composed of the following components: 115kg cement; 235kg water; 770kg sand; 770kg crushed stone; 170kg clay; 35kg bentonite; 10kg water-swelling waterstop; 5kg calcium carbonate whisker; 5kg calcium sulfate whisker; 5kg steel fiber; 3kg chrysotile asbestos; 10kg dispersant.
[0030] In this embodiment, the length of the calcium carbonate whisker is 30 μm and the diameter is 0.5 μm; the length of the calcium sulfate whisker is 100 μm and the diameter is 1 μm; the length of the steel fiber is 50 mm and the diameter is 0.2 mm.
[0031] In this embodiment, the dispersant is compounded by acrylate copolymer emulsion, sodium methyl siliconate, sodium stearate and calcium chloride in a mass ratio of 4:3:2:1, that is, the dispersant is mixed by 4kg of acrylate copolymer emulsion, 3kg of sodium methyl siliconate, 2kg of sodium stearate and 1kg of calcium chloride.
[0032] The present application also discloses a method for preparing a plastic concrete mixture for use in the construction of a dam anti-seepage continuous wall, comprising the following steps: Step 1, weigh the materials according to the above mass, and put cement, sand and gravel into a stirring kettle, stir at a speed of 60r / min for 10min, then add water, and continue stirring for 20min to obtain a premix.
[0033] Step 2, cut the water-swellable waterstop strip into uniform particles, and control the particle size of the cut particles to 2mm, then soak the granular water-swellable waterstop strip in the waterproof coating so that the waterproof coating completely immerses the water-swellable waterstop strip, soak for 5 minutes, and after the surface of the water-swellable waterstop strip is completely covered with the waterproof coating, pick up the water-swellable waterstop strip, dry it, and set it aside.
[0034] Add calcium carbonate whiskers, calcium sulfate whiskers, steel fibers, chrysotile asbestos and dispersants to the premix obtained in step 1, stir at a speed of 60 r / min for 30 min, stir evenly, then add clay, bentonite and the above-mentioned spare water-swellable waterstop strip particles while maintaining a speed of 60 r / min, continue stirring at a speed of 60 r / min for 20 min, stir evenly, and obtain a plastic concrete mixture for the construction of a dam anti-seepage continuous wall.
[0035] Example 2 The difference from Example 1 is: The dosage of each component is different, as follows: 125kg cement; 245kg water; 790kg sand; 790kg crushed stone; 190kg clay; 45kg bentonite; 15kg water-swelling waterstop; 10kg calcium carbonate whisker; 10kg calcium sulfate whisker; 8kg steel fiber; 6kg chrysotile asbestos; 15kg dispersant.
[0036] In this embodiment, the length of the calcium carbonate whisker is 40 μm and the diameter is 1 μm; the length of the calcium sulfate whisker is 105 μm and the diameter is 2 μm; the length of the steel fiber is 60 mm and the diameter is 0.5 mm.
[0037] In this embodiment, the dispersant is compounded by acrylate copolymer emulsion, sodium methyl siliconate, sodium stearate and calcium chloride in a mass ratio of 6:4:3:2, that is, the dispersant is mixed by 6kg of acrylate copolymer emulsion, 4kg of sodium methyl siliconate, 3kg of sodium stearate and 2kg of calcium chloride.
[0038] In the preparation method, step 2 controls the particle size of the particles cut from the water-swellable waterstop strip to be 5 mm.
[0039] Example 3 The difference from Example 1 is: The dosage of each component is different, as follows: 120kg cement; 240kg water; 780kg sand; 780kg crushed stone; 180kg clay; 40kg bentonite; 12g water-swelling waterstop; 7kg calcium carbonate whisker; 8kg calcium sulfate whisker; 6kg steel fiber; 5kg chrysotile asbestos; 12.5kg dispersant.
[0040] In this embodiment, the length of the calcium carbonate whisker is 35 μm and the diameter is 0.8 μm; the length of the calcium sulfate whisker is 103 μm and the diameter is 1.5 μm; the length of the steel fiber is 55 mm and the diameter is 0.4 mm.
[0041] In this embodiment, the dispersant is compounded by acrylate copolymer emulsion, sodium methyl siliconate, sodium stearate and calcium chloride in a mass ratio of 5:3.5:2.5:1.5, that is, the dispersant is a mixture of 5kg of acrylate copolymer emulsion, 3.5kg of sodium methyl siliconate, 2.5kg of sodium stearate and 1.5kg of calcium chloride.
[0042] In the preparation method, step 2 controls the particle size of the particles cut from the water-swellable waterstop strip to be 3 mm.
[0043] Example 4 The difference from Example 3 is that an equal amount of acrylic acid emulsion is used to replace the acrylic ester copolymer emulsion.
[0044] Example 5 The difference from Example 3 is that an equal amount of potassium trimethylsiliconate is used to replace sodium methylsiliconate.
[0045] Example 6 The difference from Example 3 is that sodium stearate is replaced by an equal amount of calcium stearate.
[0046] Example 7 The difference from Example 3 is that calcium chloride is replaced by an equal amount of potassium chloride.
[0047] Example 8 The difference from Example 3 is: The length of the calcium carbonate whisker is 25 μm and the diameter is 0.3 μm; the length of the calcium sulfate whisker is 110 μm and the diameter is 2.5 μm; the length of the steel fiber is 40 mm and the diameter is 0.1 mm.
[0048] Example 9 The difference from Example 3 is: The length of the calcium carbonate whisker is 45 μm and the diameter is 1.5 μm; the length of the calcium sulfate whisker is 95 μm and the diameter is 0.5 μm; the length of the steel fiber is 65 mm and the diameter is 1 mm.
[0049] Comparative Example 1 The difference from Example 3 is that the water-swellable waterstop strip is replaced by an equal amount of chrysotile.
[0050] Comparative Example 2 The difference from Example 3 is that the calcium carbonate whiskers are replaced by an equal amount of magnesium carbonate whiskers.
[0051] Comparative Example 3 The difference from Example 3 is that the calcium sulfate whiskers are replaced by an equal amount of magnesium sulfate whiskers.
[0052] Comparative Example 4 The difference from Example 3 is that the steel fibers are replaced by an equal amount of carbon fibers.
[0053] Comparative Example 5 The difference from Example 3 is that chrysotile asbestos is replaced by an equal amount of slag wool.
[0054] Comparative Example 6 The difference from Example 3 is: Replace water-swellable waterstop with an equal amount of chrysotile; Replace calcium carbonate whiskers with an equal amount of magnesium carbonate whiskers; Replace calcium sulfate whiskers with an equal amount of magnesium sulfate whiskers; Replace steel fibers with an equal amount of carbon fibers; Replace chrysotile asbestos with an equal amount of slag wool.
[0055] Experiment 1 According to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the plastic concrete mixtures prepared in the above embodiments and comparative examples for the construction of dam anti-seepage continuous walls were cast into molds and cured at 22°C for 28 days to make several prism specimens with a size of 150mm×150mm×300mm. According to 7 static compressive elastic modulus tests, the static compressive elastic modulus values (MPa) of the prism specimens prepared above were respectively tested.
[0056] Experiment 2 According to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the plastic concrete mixtures prepared in the above embodiments and comparative examples for the construction of dam anti-seepage continuous walls were cast into molds and cured at 22°C for 28 days to make several prism specimens with a size of 150 mm × 150 mm × 600 mm. According to 10 flexural strength tests, the flexural strength (MPa) of the prism specimens prepared above was tested.
[0057] Experiment 3 According to GB / T 50082-2024 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", the plastic concrete mixtures prepared in the above embodiments and comparative examples for the construction of dam anti-seepage continuous walls were cast into molds and cured at 22°C for 28 days to make several cubic specimens with a size of 100mm×100mm×100mm. According to the 14 sulfate erosion resistance test, the sulfate resistance levels of the cubic specimens prepared above were tested.
[0058] Experiment 4 According to GB / T 50082-2024 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", the plastic concrete mixtures prepared in the above embodiments and comparative examples for the construction of dam anti-seepage continuous walls were cast into molds and cured at 22°C for 28 days to make several cubic specimens with a size of 100mm×100mm×100mm. According to the 6.1 water seepage height method in the 6 water penetration resistance test, the water seepage height (mm) of the cubic specimens prepared above was tested.
[0059] The test data of the above experiments are detailed in Table 1.
[0060] Table 1 According to the data comparison of Examples 3-7 in Table 1, Examples 4-7 respectively use similar substances to replace the components of the dispersant. Although the flexural strength of Examples 4-7 is improved to a certain extent, the elastic modulus will also be greatly improved at the same time, and the impermeability and durability will also be affected to a certain extent. It is proved that by adopting specific dispersant components and compounding in a specific proportion, it is more conducive to the uniform dispersion of concrete fillers and better coordinated compounding, and it is conducive to better coordination between the water-swelling waterstop strip and other fillers, so that when the concrete is under pressure, the water-swelling waterstop strip can provide a certain elastic force, and when the concrete is subjected to bending force, rigid fillers such as whiskers and fibers can play a better role, and cooperate with each other without affecting each other, so that the concrete can have both a lower elastic modulus and a higher flexural strength; at the same time, it is also conducive to the filler stacking in the concrete to be more dense, so that the density of the concrete is higher, and thus the impermeability and durability of the concrete are better.
[0061] According to the data comparison between Example 3 and Example 8-9 in Table 1, Example 8-9 uses calcium carbonate whiskers, calcium sulfate whiskers and steel fibers of different lengths and diameters. Although the flexural strength of Example 8-9 is further improved, the elastic modulus of concrete also increases more significantly, and the impermeability and durability are also affected to a certain extent. This proves that by using fillers of specific sizes to cooperate with each other, it is beneficial for the fillers to better cooperate with the water-swelling waterstop strips, so that each can work together without affecting each other, which is beneficial for the concrete to better maintain a lower elastic modulus while having better flexural strength; at the same time, it is also beneficial for the fillers to be better stacked and compacted, so that the density of the concrete is improved, thereby better improving the impermeability and durability of the concrete.
[0062] According to the data comparison between Example 3 and Comparative Examples 1-6 in Table 1, Comparative Examples 1-5 respectively use similar substances to replace the water-swelling waterstop strips, calcium carbonate whiskers, calcium sulfate whiskers, steel fibers and chrysotile asbestos, and Comparative Example 6 uses similar substances to replace all of the above substances. Although the compressive strength is improved, the elastic modulus also increases sharply, resulting in increased brittleness of the concrete and difficulty in deformation; and after the replacement, the filler is difficult to stack densely in the concrete, which is easy to affect the density of the concrete, thereby affecting the impermeability and durability of the concrete. It is proved that only by using specific fillers in specific proportions to coordinate with each other can the water-swelling waterstop strip be better coordinated with the filler, so that the performance of the concrete is both rigid and flexible without affecting each other. At the same time, it is beneficial for the filler to be better stacked and densely inside the concrete, so that the density of the concrete is higher, and the impermeability and durability of the concrete are better.
[0063] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A plastic concrete mixture for the construction of a dam anti-seepage continuous wall, characterized in that: The composition includes the following components in parts by weight: 115-125 parts of cement; 235-245 parts of water; Sand 770-790 parts; 770-790 parts of crushed stone; Clay 170-190 parts; 35-45 parts of bentonite; 10-15 pieces of water-swelling waterstop strips; Calcium carbonate whiskers 5-10 parts; Calcium sulfate whiskers 5-10 parts; 5-8 parts of steel fiber; 3-6 parts of chrysotile; Dispersant 10-15 parts.
2. The plastic concrete mixture for the construction of dam anti-seepage continuous wall according to claim 1, characterized in that: The dispersant is prepared by compounding acrylate copolymer emulsion, sodium methylsiliconate, sodium stearate and calcium chloride.
3. A plastic concrete mixture for the construction of a dam anti-seepage continuous wall according to claim 2, characterized in that: The dispersant is prepared by compounding acrylic copolymer emulsion, sodium methylsiliconate, sodium stearate and calcium chloride in a mass ratio of (4-6): (3-4): (2-3): (1-2).
4. A plastic concrete mixture for the construction of a dam anti-seepage continuous wall according to any one of claims 1 to 3, characterized in that: The water-swellable waterstop strip is in granular form.
5. The plastic concrete mixture for the construction of dam anti-seepage continuous wall according to claim 4, characterized in that: The particle size of the water-swellable waterstop strip is 2-5 mm.
6. The plastic concrete mixture for the construction of dam anti-seepage continuous wall according to claim 5, characterized in that: The surface of the water-swellable waterstop strip particles is also covered with a waterproof coating.
7. A plastic concrete mixture for the construction of a dam anti-seepage continuous wall according to any one of claims 1 to 3, characterized in that: The length of the calcium carbonate whisker is 30-40 μm, and the diameter is 0.5-1 μm; the length of the calcium sulfate whisker is 100-105 μm, and the diameter is 1-2 μm.
8. A plastic concrete mixture for the construction of a dam anti-seepage continuous wall according to any one of claims 1 to 3, characterized in that: The steel fiber has a length of 50-60 mm and a diameter of 0.2-0.5 mm.
9. A method for preparing a plastic concrete mixture for use in the construction of a dam anti-seepage continuous wall as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1, first mix cement, sand and gravel and stir evenly, then add water and stir evenly to obtain a premix; Step 2, adding calcium carbonate whiskers, calcium sulfate whiskers, steel fibers, chrysotile asbestos and dispersants into the premix while stirring, stirring evenly, and then adding clay, bentonite and water-swellable waterstop strips in sequence while stirring evenly to obtain a plastic concrete mixture for the construction of a dam anti-seepage continuous wall.
10. The method for preparing a plastic concrete mixture for the construction of a dam anti-seepage continuous wall according to claim 9, characterized in that: In step 2, the water-swellable waterstop strips are pretreated by cutting them into granules, and then the granular water-swellable waterstop strips are immersed in a waterproof coating. After the surfaces of the water-swellable waterstop strips are covered with the waterproof coating, the water-swellable waterstop strips are picked up, dried, and set aside.